Pseudodacryocystitis: paediatric case series of infected atypical ethmoid air cells masquerading as recurrent dacryocystitis - Mohite, A (Eye (Lond), 2017)
PURPOSE: To highlight the clinical and surgical considerations in treating patients with apparent recurrent acute dacryocystitis with a patent lacrimal system. METHODS: Three children referred to a tertiary unit as recurrent acute dacryocystitis were reviewed retrospectively. Imaging and subsequent surgical intervention revealed the underlying diagnosis. RESULTS: All three cases presented with recurrent abscesses in the region of the lacrimal sac that failed to respond to incision and drainage. The lesions were lower and more lateral to the usual location of a sac abscess and closer to the inferior orbital rim. All three cases were found to have patent lacrimal systems on syringing, and all were found to have infected, low-lying, anteriorly placed aberrant ethmoid air cells on computed tomography and magnetic resonance imaging. These were confirmed on subsequent surgical exploration. CONCLUSIONS: Infected low-lying ethmoid air cells can mimic dacryocystitis with recurrent abcesses. In cases where a patent nasolacrimal system is demonstrated and a more inferolateral location of the swelling than would be expected in dacryocystitis is seen, imaging is warranted to ensure the appropriate intervention is undertaken. Anterior ethmoidectomy as opposed to dacryocystorhinostomy is the appropriate treatment in these cases.